(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2015)
Silica gel based sorbent (SG) sequentially modified by polyhexamethylene guanidine (PHMG) and xylenol orange (XO) was obtained. It is found that XO quantitatively recover from solution in a wide range of pH 3-7, which corresponds to its presence in solution in anionic form. Fixation of XO on SG-PHMG-surface is realized due to electrostatic interaction between guanidine groups of the sorbent surface with sulfo- and carboxyl groups of the dye. Quantitative desorption of XO occurs in the dynamic conditions by 0.1 m HCl. Sorption of vanadium (V) occurs in the form of anion VO3-. Reduction of contents of this form, which occurs in subacid and alkalescent conditions, leads to a decrease in the degree of extraction of vanadium. Quantitative sorption of vanadium in dynamic mode occurs in the range of pH 3.5-6 whereas in static conditions, maximal sorption observed at pH range of 4-5 and is only 77%. Distribution coefficient in optimal pH conditions for dynamic sorption is 2.3∙104 cm3/g. Desorption of vanadium from the surface of the sorbent using 1M HCl in static conditions is quantitative and allows to conduct its further determination by spectrophotometric method. Characteristics of the obtained sorbent is not inferior chemically modified silica with iminodiacetic acid groups, however, has a significant advantage in simplicity and environmental security of synthesis, low cost and availability of consumables and the possibility of determination of vanadium(V) directly after desorption by spectrophotometric method.